Absent end diastolic flow: progression and perinatal outcome at a tertiary referral centre. (7th June 2011) - Mullins, E; Paramasivam, G; Zhang, E; Prior, T; Kumar, S
Abstract : Introduction: Absent end diastolic flow (AEDF) results from obliteration of around 60% of placental circulation and represents a major pathological sign in fetal management. Methods: Retrospective cohort study of maternity database. Maternal demographics, scan to delivery interval, umbilical artery flow, fetal and neonatal outcomes were recorded. Fetocide, IUD/SB, neonatal death and infant death were grouped as a composite mortality outcome. Factors were tested in univariate analyses, and multivariate models were constructed using backward stepwise logistic regression in SPSS v17. Results: 117 fetuses with AEDF delivered at QCCH between January 2003 and August 2010. Median gestation at detection of AEDF was 27+1 weeks (15+4 to 38+1 weeks). Median time period from diagnosis to delivery was 11 days. 65.2% were admitted to the neonatal unit. 80.4% were liveborn (5.1% neonatal deaths, 1.7% infant deaths), 19.6% stillborn (3.4% fetocide), 53% female, 47% male. Gestation at delivery (OR 0.59/week, p>0.001), weight at delivery (OR 0.02/kg, p>0.001, CI 0.002 to 0.17), progression from AEDF to REDF (OR 2.53, p=0.049, CI 1.01 to 6.372) and male sex (OR 2.32, p=0.05, CI 1.1 to 5.4) were significantly associated with composite mortality. Multivariate analysis showed these effects to be due to gestation at delivery. Neonatal unit admission was not significantly associated with any of the measured variables. Discussion: 26/117 fetuses progressed to REDF, later gestation at diagnosis was associated with lower chance of progression. (p=0.009, OR 0.84, CI 0.74 to 0.96) This is likely due to conservative management of fetuses diagnosed at early gestation with AEDF and delivery of fetuses with AEDF at later gestation. Prematurity was the significant association with poor outcome for these IUGR fetuses.